Conceptos médicos en Purgatorio XXV, vv. 37-78. Las virtudes y el desarrollo vital del feto. - Iglesias Rondina, María Clara (Cuadernos de Filología Italiana, 2007)
A passage from Divina Commedia (Purgatorio XXV, vv. 37-78) is analyzed that presents different reading problems, especially those related to doctrinal and medical aspects of medieval thought. Doctrinal problems are connected with the reception of the three animae (vegetative, sensitive and intellective souls) in the womb, and with the consequences derived from this fact. Medical problems are related to foetus’ formation, development and evolution, and to the adquisition of certain characteristics that determine its nature. This paper analyzes these problems, by comparing some relevant elements to fundamental texts of medieval medical knowledge, general science, Christian doctrine and other works by the same author.